Sudden hypertension in a kidney transplant recipient after a skiing accident. (2016) - Meier, Markus; Hunold, Peter; Nitschke, Martin
Abstract: Introduction: Complications after renal transplants are frequent. A well-known but less frequent complication is arteriovenous fistula formation, which can remain asymptomatic or present with hematuria, hypertension, or renal insufficiency. Presentation of case: We present the case of a young, male kidney transplant recipient with newly developed hypertension due to the formation of an arteriovenous fistula a long period after the last renal biopsy. Discussion: In our case, the sonographic evaluation showed the aliasing phenomenon, which was useful in the detection of the AVF. Superselective transcatheter embolization is considered to be the treatment of choice in such cases and has been proven to be safe and effective, even in long-term evaluations. Conclusion: Our findings in this case highlight a rarely reported clinical presentation which physicians should be aware of when evaluating patients who have received a renal transplant.